2012
DOI: 10.1016/j.jprot.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals cellular pathways regulating carbohydrate metabolism that are modulated in primary human skeletal muscle culture due to treatment with bioactives from Artemisia dracunculus L.

Abstract: Insulin resistance is a major pathophysiologic abnormality that characterizes metabolic syndrome and type 2 diabetes. A well characterized ethanolic extract of Artemisia dracunculus L., termed PMI 5011, has been shown to improve insulin action in vitro and in vivo, but the cellular mechanisms remain elusive. Using differential proteomics, we have studied mechanisms by which PMI 5011 enhances insulin action in primary human skeletal muscle culture obtained by biopsy from obese, insulin-resistant individuals. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…Moreover aqueous extract of Artemisia capillaries has shown a hepatoprotective effects on FFR [10]. Artemisia extract affected on insulin sensitivity, modulating of carbohydrate metabolism and glucose influx [11]. Investigation revealed that Artemisia extracts had shown hepatoprotective and hypolipidemic properties and antioxidative activity in hepatoma cells in Dgalactose-induced oxidative stress in mouse model [12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover aqueous extract of Artemisia capillaries has shown a hepatoprotective effects on FFR [10]. Artemisia extract affected on insulin sensitivity, modulating of carbohydrate metabolism and glucose influx [11]. Investigation revealed that Artemisia extracts had shown hepatoprotective and hypolipidemic properties and antioxidative activity in hepatoma cells in Dgalactose-induced oxidative stress in mouse model [12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…Fifty microgram of protein from each sample was digested with trypsin and labeled with iTRAQ™ labeling reagents as per manufacturer's instructions (AB SCIEX, Foster City, CA) [16]. Briefly, protein extracts in TEAB buffer (2 νg/μL) from each of the four HSkMC samples were denatured using 2% SDS and reduced with 50 mM Tris (2-carboxyethyl) phosphine (TCEP).…”
Section: Methodsmentioning
confidence: 99%
“…Previous proteomics studies show that PMI 5011 treatment increases abundance of proteins involved in glycolysis pathway and increases glucose uptake and metabolism via enhanced translocation of glucose transporter 4 (GLUT4) into the plasma membrane. Both gel-based and gel-free proteomics analyses also showed that PMI 5011 exhibits anti-inflammatory action by reducing levels of proteins participating in the NFkB pathway [15,16]. As recognized, protein phosphorylation is an important post-translational modification that controls activation and deactivation of proteins and their subcellular localization to regulate metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins were up regulated in diabetic condition and the authors have reported the value of proteomic approach in identifying them also as potential markers for various types of diseases [72]. Proteins involved in regulating inflammatory pathways were obtained from the ethanolic extract of Artemisia dracunculus L. (PMI 5011) using differential proteomics data by Kheterpal et al [73] and Scherp et al 2012 [74]. They have shown that this extract modulates proteins involved in regulating inflammatory pathways and regulate carbohydrate metabolism in human skeletal muscle culture, respectively [73,74].…”
Section: /6mentioning
confidence: 99%
“…Proteins involved in regulating inflammatory pathways were obtained from the ethanolic extract of Artemisia dracunculus L. (PMI 5011) using differential proteomics data by Kheterpal et al [73] and Scherp et al 2012 [74]. They have shown that this extract modulates proteins involved in regulating inflammatory pathways and regulate carbohydrate metabolism in human skeletal muscle culture, respectively [73,74]. Panax ginseng has been used to treat diabetes [75].…”
Section: /6mentioning
confidence: 99%